"Fencing is our last stronghold before we lose it all." A political ecology of fencing around the Maasai Mara National Reserve, Kenya. (September 2019) - Weldemichel, Teklehaymanot G.; Lein, Haakon
Highlights: Historical views that stigmatize local practices push people to seek privatization. Privatization made land tradable and led to the introduction of conservancies. Conservancies further pushed some locals into smaller spaces. Fencing emerged as a way of protecting livelihoods against this trend. Abstract: In the Maasai Mara National Reserve, a state-controlled protected area in Kenya, and in its surroundings, a particular concern in recent years has been the proliferation of fencing in what once was an open landscape. The fencing poses challenges to both wildlife and the traditional pastoralism practised by Maasai communities, which were dependent on the presence of open communal land. The purpose of the article is to identify the root causes of the enclosure of former common land and the increasing fencing of plots of land owned by individual Maasai. The study is based on empirical material from extended fieldwork conducted in two villages adjacent to the reserve and a review of relevant documents. The main finding is that the history of land division, the introduction of wildlife conservancies, and the materialization of an ageold discourse about the 'end of pastoralism', through the process of privatization and commercialization of land, have played major roles in pushing the Maasai to fence their land. The authors conclude that fencing can be seen both as an active form of resistance to dispossession in the name of conservation and as evidence of the acceptance of the discourse on the 'end of traditional pastoralism', which has been promoted by a range of state and nonstate actors since Kenya gained independence from colonial rule.